HORIZONTAL MERGERS AND WEAK AND STRONG COMPETITION COMMISSIONS - Ristić, Bojan; Trifunović, Dejan (Economic Annals, 2014)
In this paper we analyse the horizontal merger of companies in an already concentrated industry. The participants in mergers are obliged to submit notification to the Competition Commission but they also have the option of rejecting the merger. At the time of the notification submission the participants do not know whether the Commission is strong or weak, and they can complain to the Court if the Commission prohibits the merger. We model the strategic interaction between Participants and Commission in a dynamic game of incomplete information and determine weak perfect Bayesian equilibria. The main finding of our paper is that Participants will base their decision to submit notification on their belief in a weak Commission decision and will almost completely ignore the possibility of a strong Commission decision. We also provide a detailed examination of one case from Serbian regulatory practice, which coincides with the results of our game theoretical model.